Studi Komparasi Self-Esteem Pengguna Iphone dan Bukan Pengguna Iphone pada Remaja - Azhar El Hami; Asep Ahmad Sidik (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2017)
IPhone as one of the smartphone brand, is often regarded as a prestigious symbol for teenagers. In choosing goods, teenagers also pay attention to the symbolic value that they want to show. These symbols give a certain impact to their self-esteem among teenager. What about the non-iPhone user? The purpose of this study was to see the difference of self-esteem between iPhone users and non-iPhone users. The samples are the students in one of public high school at Garut. The design of this study is quantitative non-experimental with comparative method. The study compared two groups of teenagers: iPhone users (N = 25) and non-iPhone users (N = 39). All respondents filled out three questionnaires about IPhone Brand Image, Self-Esteem Questionnaire and Self-Esteem iPhone Ownership (SEiO) Questionnaire. The data obtained were tested by t-test on two groups. The results show that there are significant differences of self-esteem between two groups.